Annotations of Connectives and Arguments in Malayalam Language. (2016) - Sheeja, S. Kumari; Devi, Sobha Lalitha
Abstract: Discourse relations in natural languages link clauses in text and compose overall text structure. Discourse connectives are an important part of modeling the Malayalam discourse structure. We followed the annotation procedure of Penn Discourse Tree Bank and worked on tagging of discourse connectives and arguments of Malayalam text and also report the senses of relation. We present our work on annotations of Malayalam discourse connectives and arguments which helps to know more about the discourse connectives and their appearance in case of semantic rules in Malayalam discourse. Discourse connectives may or may not be explicitly present in the relation. In our work, we focus on the annotation of both explicit and implicit connectives and arguments in Malayalam text and showed encouraging results.